Malaysian bilateral exports and bilateral real exchange rates - Yusoff, Mohammed (2007)
This paper analyzes the performance of Malaysian bilateral exports to its major importing countries: the United States, Japan, and Singapore and then investigates whether the export performance could be improved through depreciation or devaluation of domestic currency using co-integration technique and VECM. The co-integration test suggests that real exports, real exchange rates, real imports, and foreign income are co-integrated. The estimated long-run export equations indicate that the real exchange rates, real foreign income, and real imports are important determinants of exports. The major policy implication from this study is that a devaluation or depreciation of ringgit could improve the competitiveness of Malaysian exports.